A combined approach for predicting the cytotoxic effect of drug-nanoaggregates. Issue 40 (28th September 2016) - Wojnilowicz, M.; Tortora, M.; Bobay, B. G.; Santiso, E.; Caruso, M.; Micheli, L.; Venanzi, M.; Menegatti, S.; Cavalieri, F.
Abstract : Polymer carriers induce assembly of drugs into nanoaggregates and play a role in tuning the architecture and bioactivity of drug nanoaggregates. Abstract : We present a combined spectroscopic and computational approach aimed to elucidate the mechanism of formation and activity of etoposide nanoaggregates upon release from dextran–etoposide conjugates. Etoposide is an anticancer drug that inhibits cell growth by blocking Topoisomerase II, the key enzyme involved in re-ligation of the DNA chains during the replication process. In silico and spectroscopic analysis indicate that released etoposide nanoaggregates have a different structure, stability, and bioactivity, which depend on the pH experienced during the release. Molecular dynamics simulation and in silico docking of etoposide dimers suggest that the aggregation phenomena inhibit etoposide bioactivity, yet without drastically preventing Topoisomerase II binding. We correlated the diminished cytotoxic activity exerted by dextran–etoposide conjugates on the A549 lung cancer cells, compared to the free drug, to the formation and stability of drug nanoaggregates.